daf-31 Encodes the Catalytic Subunit of N Alpha-Acetyltransferase that Regulates Caenorhabditis elegans Development, Metabolism and Adult Lifespan - Chen, Di (Public Library of Science, 2014)
The Caenorhabditis elegans dauer larva is a facultative state of diapause. Mutations affecting dauer signal transduction and morphogenesis have been reported. Of these, most that result in constitutive formation of dauer larvae are temperature-sensitive (ts). The daf-31 mutant was isolated in genetic screens looking for novel and underrepresented classes of mutants that form dauer and dauer-like larvae non-conditionally. Dauer-like larvae are arrested in development and have some, but not all, of the normal dauer characteristics. We show here that daf-31 mutants form dauer-like larvae under starvation conditions but are sensitive to SDS treatment. Moreover, metabolism is shifted to fat accumulation in daf-31 mutants. We cloned the daf-31 gene and it encodes an ortholog of the arrest-defective-1 protein (ARD1) that is the catalytic subunit of the major N alpha-acetyltransferase (NatA). A daf-31 promoter::GFP reporter gene indicates daf-31 is expressed in multiple tissues including neurons, pharynx, intestine and hypodermal cells. Interestingly, overexpression of daf-31 enhances the longevity phenotype of daf-2 mutants, which is dependent on the forkhead transcription factor (FOXO) DAF-16. We demonstrate that overexpression of daf-31 stimulates the transcriptional activity of DAF-16 without influencing its subcellular localization. These data reveal an essential role of NatA in controlling C. elegans life history and also a novel interaction between ARD1 and FOXO transcription factors, which may contribute to understanding the function of ARD1 in mammals.